UPAYA MENINGKATKAN KEMAMPUAN MENJAWAB PERTANYAAN MELALUI PENERAPAN KARTU SOAL, PENDEKATAN SAINTIFIK DANPENDEKATAN KETERAMPILAN PROSES PADA PELAJARAN BAHASA INDONESIA SISWA KELAS X1 PENJUALAN 1 TAHUN 2014/2015 - Khosim Khosim (Lembaga Penelitian UM Metro, 2016)
The use of the approach is very important in the success of learning. The learning activity will effective and efficient if supported by the proficiency teachers that organize learning approach. How to set teacher’s approach in learning activity is very influential to the way students learn. The research aims are: (1) Developed a model of learning, i,e the application of card problem and process skills approach, (2) Increasing the ability of students to aswer the question, (3) Increasing the activities of students in the learning process, (4) Increasing the performance of the teacher. The data collection is done through observation, quistionaire,interview, test, and documentation. From the analysis of the data, it was obtained the conclusion that learning by using card problem and process skills approaches were able: (1) To contribute positively to improving the ability to answer the question of Bahasa Indoneesia subjects, (2) To incease the active partipsipation of students in the learning process, (3) To improve student learning outcomes, and, (4) To provide a positive influence on performance improvement of teachers.